Implementation Tolerance in Islamic Education at the Bali Bina Insani Islamic Boarding School - Zulfa, Nur Roihanah; Zurley, Zianna; Azizatul, Wafiq; Abshor, Ulil; Roziqin, Muhammad; Arifin, Zaenal (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2023)
Multiculturalism is a plurality in life, one of which is found in the Bali Bina Insani Islamic Boarding School, in this study the author wants to know how the Bina Insani Bali Islamic Boarding School implements the values of tolerance in Islamic education into daily life, as well as what obstacles are faced by the Islamic boarding school and how the efforts are made. to get over it. In this study the authors used qualitative research. The type of research is field research. In collecting the required data, the researcher used three techniques, namely using field observations, interviews, and documentation and supported by literacy from books and scientific journals. The results of this study indicate the values of tolerance in Islamic education contained in the Bali Bina Insani Islamic Boarding School including 1) Respecting the beliefs held by the local community. 2) Enforce regulations for their students by forbidding their students to wear santri attributes such as wearing a cap when leaving the pesantren environment. 3) Not allowed to use TOA in all pesantren activities. 4) Replacing the sacrificial cow with a goat. 5) Islamic boarding schools also participate in social activities in the community around the cottage. The Bali Bina Insani Islamic Boarding School grew up in a community where the majority of the population embraced Hinduism and had experienced obstacles in its development. Among them are lack of trust from the community and consider Islamic boarding schools as a threat. For this reason, Islamic boarding schools apply the values of tolerance and embrace the surrounding community so that these obstacles can be eroded.